Usode vodij krajevnih skupin Štajerske domovinske zveze v ptujskem okrožju po drugi svetovni vojni - Chomicki, Špela (Studia Historica Slovenica, 2024)
Drawing on archival sources, newspaper sources and academic literature, this paper examines the period of the Second World War and its first post-war year. The authors begin with a presentation of the German occupation of Lower Styria, the establishment of the occupation administration and the Styrian Homeland Union. The latter was organised into f ive districts, made up of smaller local groups. At the core of the paper, the authors focus on the different fates of the leaders of the local groups in the Ptuj district just after the end of the Second World War. The main aim of the paper is to show the multifaceted and complex nature of inter-war and post-war events in the Ptuj district through a variety of examples.
Keywords: druga svetovna vojna; inter-war violence; leaders of local groups; medvojno nasilje; occupation of Lower Styria; okupacija Spodnje Štajerske; post-war violence; povojno nasilje; Second World War; Styrian Homeland Union; Štajerska domovinska zveza; vodje krajevnih skupin